Socio-Economic Factors and Knowledge Influencing Newborn Care Practices: Experience at Dhaka Shishu Hospital (Ibrahim Medical College Journal, 2010)
Reducing maternal and neonatal mortality remains a big challenge for a developing country likeBangladesh. Mothers’ knowledge in neonatal care plays an important role in bringing down themortality as well as morbidity. This study was conducted in Dhaka Shishu Hospital during theperiod of December 2007 to February 2008 and was based on primary data collected on socioeconomicstatus, knowledge and practice of mothers of neonates attending the hospital. A total of 400 motherswere interviewed. More than fifty percent mothers had an appropriate knowledge on feeding neonates,hand washing before handling neonates, care of eye, care of umbilicus and they were practicing aswell. Where as less than fifty percent mothers had appropriate knowledge on keeping neonateswarm, cutting hair, bathing, vaccination, oil massage and their practice rate also commensuratewell with their knowledge level. Majority of the mothers were in the age group of 21-25 years,having completed primary education or passed SSC exam. They were house wives living in an urbanarea, with a monthly family income of 3000-7000 taka. Statistically significant association wasfound between socio demographic variables and knowledge and practices on neonatal care of themothers.Ibrahim Med. Coll. J. 2010; 4(1): 17-20Key words: Socio-economic factors; knowledge and practices; neonatal careDOI: 10.3329/imcj.v4i1.5930